An overview on the study of the representations of early ulamas in the Malay world to religions other than Islam - Abdul Jalil, Mohd. Noh; Mohd Amin, Wan Mohd Azam (Universiti Sains Islam Malaysia (USIM), 2017)
This article attempts to give an overview on the study of the representations of early Malay ulamas in the Malay Archipelago to religions other than Islam. The ability of these ulamas to transform the Malay world from the influence of Hindu-Buddhist and traditional beliefs to Islam offers interesting prospects to such study. Two main challenges have been identified, namely the problems in dealing with early Malay evidence as well as problems on issues and theories of the Islamization of the Malay Archipelago. The analysis on these challenges will be made on selected early Malay texts as well as on the existing theories of the arrival of Islam in the Malay Archipelago. This study concluded that the understanding on both challenges will provide a less speculative answer as to how well early Malay Muslims responded to the arrival of this foreign religion in their life and adopted and adapted it.